2020
DOI: 10.1101/2020.01.22.915942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A universal chromosome identification system for maize and wildZeaspecies

Abstract: Maize was one of the first eukaryotic species in which individual chromosomes can be identified cytologically, which made maize one of the oldest models for genetics and cytogenetics research. Nevertheless, consistent identification of all 10 chromosomes from different maize lines as well as from wild Zea species remains a challenge. We developed a new technique for maize chromosome identification based on fluorescence in situ hybridization (FISH). We developed two oligonucleotide-based probes that hybridize t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…The nine chromosome painting probes were labeled by either digoxigenin or biotin, and detected using red and green fluorescence, respectively (Braz et al ., 2020a). A group of two or three probes (the third probe was labeled 50% digoxigenin and 50% biotin) were hybridized to metaphase chromosomes prepared from root tips of germinated seeds of C. maxima .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nine chromosome painting probes were labeled by either digoxigenin or biotin, and detected using red and green fluorescence, respectively (Braz et al ., 2020a). A group of two or three probes (the third probe was labeled 50% digoxigenin and 50% biotin) were hybridized to metaphase chromosomes prepared from root tips of germinated seeds of C. maxima .…”
Section: Resultsmentioning
confidence: 99%
“…These oligos can then be synthesized in parallel and labeled as a FISH probe (Han et al ., 2015). Chromosomal research based on such pooled oligo probes has been reported in a rapidly increasing number of plant species (Qu et al ., 2017; Braz et al ., 2018; He et al ., 2018; Hou et al ., 2018; Meng et al ., 2018; Xin et al ., 2018; Albert et al ., 2019; Martins et al ., 2019; Simonikova et al ., 2019; Bačovský et al ., 2020; Bi et al ., 2020; Braz et al ., 2020a; Liu et al ., 2020; Song et al ., 2020; Xin et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root tips were harvested from plants and treated with N 2 O at a pressure of 160 psi ( c . 10.9 atm) for 2 h (Kato, 1999; Braz et al ., 2020a,b). The root tips were fixed in fixative solution (ethanol : acetic acid, 3 : 1) and kept at −20°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Oligo‐FISH was conducted using the previously developed maize barcode FISH probe (Braz et al ., 2020a) and two haplotype‐specific probes for maize chromosome 10 (Martins et al ., 2019). Combination of these two probes allowed identification of individual copies of chromosome 10 and their origination from either inbred B73 or H99.…”
Section: Methodsmentioning
confidence: 99%